Non-penetrative blood container and apparatus for vacuuming the same - Abu Talib, Abd. Rahim; Yahaya, Mohd Saleh; Abdul Rahman, Mohd Nazim; Abdullah, Ummi Noor Nazahiah; Adam, Siti Aishah (2010)
A non-penetrative vacuum blood container for storing blood sample, the non-penetrative vacuum blood container comprises: (a) a cap (1)having a number of air passages (4)at its inner wall and ridges (5) at is outer wall; (b) an enclosure (2) which includes enclosure head (8), enclosure neck (9) and enclosure chamfer (10); and (c) a tube (3)for storing blood sample; wherein the air passages (4) further includes enclosure stopper (7) close to opening (6) of the cap (1); and wherein an enclosure opening (11) is provided at the enclosure head.